2017
DOI: 10.1007/s12185-017-2231-3
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin suppression in β-thalassemia is associated with the down-regulation of atonal homolog 8

Abstract: Atonal homolog 8 (ATOH8) is defined as a positive regulator of hepcidin transcription, which links erythropoietic activity with iron-sensing molecules. In the present study, we investigated the association between hepcidin and ATOH8 expression in β-thalassemia. We found that inhibition of hepcidin expression in β-thalassemia is correlated with reduced ATOH8 expression. Hepatic hepcidin 1 (Hamp1) and Atoh8 mRNA expression were down-regulated in β-thalassemic mice. Hepcidin (HAMP) and ATOH8 mRNA expression were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Taken together, green tea polyphenols and curcuminoids present in the drink could possibly interfere absorption of dietary iron and mobilize delivery of iron to the erythrons [65,79,119]. Taken all our studies, we summarize the applications of nutraceutical green tea extract for the amelioration of iron-overloaded cells, β-thalassemic mice, and patients with β-thalassemia (Figure 5) [79,84,106,116,[119][120][121][122][123][124][125][126][127][128]. In our expectations, we hope the patients will have safer chelation therapy, a better quality of lives, and good health.…”
Section: Patients With β-Thalassemiamentioning
confidence: 77%
“…Taken together, green tea polyphenols and curcuminoids present in the drink could possibly interfere absorption of dietary iron and mobilize delivery of iron to the erythrons [65,79,119]. Taken all our studies, we summarize the applications of nutraceutical green tea extract for the amelioration of iron-overloaded cells, β-thalassemic mice, and patients with β-thalassemia (Figure 5) [79,84,106,116,[119][120][121][122][123][124][125][126][127][128]. In our expectations, we hope the patients will have safer chelation therapy, a better quality of lives, and good health.…”
Section: Patients With β-Thalassemiamentioning
confidence: 77%
“…ATOH8 gene, is a positive regulator of hepcidin transcription in the liver, which maintains iron homeostasis through regulating its own synthesis 20 . It has been reported that, hepcidin and ATOH8 expressions are downregulated in β thalassemia mice 21 . Mutation in this gene may causes the iron overload in the subject.…”
Section: Resultsmentioning
confidence: 98%
“…We have previously demonstrated that hepatic Hamp1 mRNA suppression is associated with a down−regulation of atonal homolog 8, which is a positive regulator of hepcidin transcription that links erythropoiesis with iron−responsive molecules in response to iron−loading anemias (e.g., thalassemia) (Upanan et al, 2015). Inversely, the Hamp1 expression was significantly up−regulated in the BKO mice treated with a combination of GTE and DFP (Upanan et al, 2017). Interestingly, Kim and colleagues showed that EGCG treatment induced expression and its production of small heterodimer partner-interacting leucine zipper protein in hepatocytes, subsequently turning on bone morphogenetic protein 6−mediated SMAD1/5/8 transactivation of the hepcidin gene, and consequently increasing the hepcidin secretion from the hepatocytes (Kim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%